2010
DOI: 10.1016/j.inhe.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and beliefs about onchocerciasis among rural inhabitants in an endemic area of Ethiopia

Abstract: A cross-sectional study was conducted to assess the knowledge and beliefs about causes, transmission, prevention and control of onchocerciasis among rural inhabitants in an endemic area of Ethiopia. Descriptive and quantitative information was collected using focus group discussions and a pretested structured questionnaire. Onchocerciasis affected and unaffected respondents' knowledge and beliefs regarding onchocerciasis were compared. Overall, 75.9% (192/253) of study subjects were aware about onchocerciasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
3
2
Order By: Relevance
“…Generally, health education about the endemicity of the disease leads to awareness and provides the necessary information for change in beliefs, attitudes and behaviour (Karunamoorthi, Kassa, & Endale, 2010;Okwa, Olusola, & Adelani, 2009). Consistent with our findings, other studies have shown that people with little or no formal education tend to believe in a wide range of misconceptions about the causes and method of transmission of onchocerciasis (Yirga et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Generally, health education about the endemicity of the disease leads to awareness and provides the necessary information for change in beliefs, attitudes and behaviour (Karunamoorthi, Kassa, & Endale, 2010;Okwa, Olusola, & Adelani, 2009). Consistent with our findings, other studies have shown that people with little or no formal education tend to believe in a wide range of misconceptions about the causes and method of transmission of onchocerciasis (Yirga et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…More than half of our study participants had the misconception that hygiene is a preventive measure. Only 5.6% of the participants reported avoiding contact with stream water as a preventive measure, which contrasts a study done in Giesha Kebele river basin, Oromia region, Ethiopia (46.2%) [ 24 ]. The probable reason could be differences in access to health information, study period, and programme implementation.…”
Section: Discussioncontrasting
confidence: 68%
“…According to a previous report from Ethiopia, onchocerciasis causes poor school performance and a high dropout rate among afflicted children, as well as severe social stigmatization, particularly among women [9]. e disease's incidence is linked to activities that expose people to vectors, such as farming, washing clothes near a river, and swimming [10].…”
Section: Introductionmentioning
confidence: 99%